Preface - Edwards, R. Randle (Columbia Journal of Asian Law, 1987)
Chinese law has attracted and mystified foreign legal scholars and merchants for hundreds of years. During the age of Voltaire, Chinese legal and political institutions were widely admired from afar. Europeans at that time had very little real knowledge of the actual substance and administration of China's imperial codes. Yet, they assumed that a country so rich in culture and material wealth must have an excellent and highly advanced legal system. By the early nineteenth century, however, Western merchants were complaining bitterly about Chinese law - the criminal law was perceived as harsh, civil and commercial law as inadequate and the courts as inaccessible to foreigners.